Focusing executive education on corporate perceptions of priorities and skills in sustainability - Simaens, A.; Bento, P.; Amaral-Baptista, M.; Duarte de Almeida, I.; Pernas, G.; Silva, J.; Leite, M. (Proceedings of the 22nd International Sustainable Development Research Society Conference, ISDRS 2016, 2016)
The term sustainability is used in this study as a multidimensional and integrated concept in three dimensions: Economic, Environmental and Social, in reference to the triple bottom line of “profit”, “planet” and ”people” (Elkington, 1999). Focusing the debate on both priorities and skill needs on sustainability matters, this study aimed at identifying issues that are worth further exploring in the context of corporate sustainability from a corporate perspective. Thus, the study specifically takes stock of priorities identified by managers in Portuguese organizations, as well as its perception of skills needs. Methodologically, the research pursued a survey strategy with an exploratory purpose aiming at closing the gap between the real world view on sustainability and the focus of executive education. This means aligning the perceptions of the managers in terms of the priorities and skill needs in the corporate world with what is offered by the executive education. The construction of the questionnaire in the dimensions of sustainability followed the international reporting framework G4 of the Global Reporting Initiative (GRI), as it was considered to be the most comprehensive framework in this area. Questionnaires were applied to a convenience sample, based on existing institutional databases. The questionnaire was online in Qualtrics platform from mid-September to mid-October 2015. The final sample consisted of 149 respondents. In summary, although this is an exploratory study, it can be concluded inter alia that: 1) when analyzed globally, the highest priority goes for the economic dimension, followed by the social and, lastly, the environmental ones; 2) There tends to be an alignment between the priorities identified and the skills needs, although perceptions of need for skills reveal higher average (with few exceptions); 3) The evaluation of suppliers appears, in various dimensions, consistently near the bottom in terms of priorities and skills needs. Since this is a first approach, the analysis of the results raise several issues requiring greater depth in future studies. For instance, an illustration of a future avenue of research raised by this study is the need for further research on the motives behind the lack of priority given to the evaluation of suppliers in its different dimensions. The issue of sustainability in the supply chain, and more precisely traceability has been explored in the literature (e.g. Pagell and Wu, 2009). Traceability refers to the identification and tracking of the supplies from the origin into its final stage, i.e. an end to end view that crosses over the independent businesses boundaries by focusing on significant overall business processes. Indeed, many companies are now focusing on their supply chains looking for Economic, Environmental and Social impacts. Thus, it looks relevant to further investigate the drivers of this phenomenon and to extract the consequences of this finding to the executive education in order to adjust both practices and syllabuses as the main outcome